Pastoral leadership lessons from Bonhoeffer: The alt‐right, the twitter mob, and ressentiment. Issue 2 (28th May 2020) - Root, Andrew
Abstract: Dietrich Bonhoeffer's radio address "The Younger Generation's Altered Conception of the Führer, " has much to teach us about what kind of pastoral leadership is needed in our present social and political contexts. Personal antipathies have blossomed into generational antinomies, and the resentments of one side versus another threaten to take over our perceptions of reality and perhaps even reality itself. In looking at Bonhoeffer's diagnosis of why the "younger generation" was seeking a strong‐man leader to help them demolish the adversaries who had aggrieved them, we can see ourselves. In listening to Bonhoeffer's cure, we may find our own medicine.